MODEL PERTUNJUKAN BARONGAN ANAK SEBAGAI TRANSMISI BUDAYA DAERAH - Karyono Karyono (Greget, 2013)
This study is in the form of â€œaction researchâ€ which focuses on the result of the study byplacing data in the form of a childrenâ€™s performance of Barongan as the material to be processed.Barongan is a folk art from Blora which has strong roots in the local community. In Blora, it is akind of communal art activity in which almost every neighbourhood has its own Barongan group.This is connected with the local belief that Barongan has the ability to protect the community, asreflected in the ritual ceremony Lamporan. In the past, Barongan has only been performed as aprocession, either as part of a ritual or to celebrate important national days. After seeing howchildren play with a toy Barongan and imitate its movements, the writer had the idea to carry outresearch and to design a model for a childrenâ€™s Barongan performance. The model of a Baronganperformance for children needs to be introduced to the community as a means of regeneration andpreservation of a local culture. The method of research used was a method of experimentation andformation in which the method of experimentation was used to find an alternative performancemodel and the method of formation was used to create a performance model.